Geochemical and mineralogical assessment of sedimentary limestone mine waste and potential for mineral carbonation - Mohd Isha, Nabila Syuhada; Mohd Kusin, Faradiella; Ahmad Kamal, Nurfakhira Meor; Syed Hasan, Sharifah Nur Munirah; Molahid, Verma Loretta M. (Springer, 2021)
This paper attempts to evaluate the mineralogical and chemical composition of sedimentary limestone mine waste alongside its mineral carbonation potential. The limestone mine wastes were recovered as the waste materials after mining and crushing processes and were analyzed for mineral, major and trace metal elements. The major mineral composition discovered was calcite (CaCO3) and dolomite [CaMg(CO3)2], alongside other minerals such as bustamite [(Ca,Mn)SiO3] and akermanite (Ca2MgSi2O7). Calcium oxide constituted the greatest composition of major oxide components of between 72 and 82%. The presence of CaO facilitated the transformation of carbon dioxide into carbonate form, suggesting potential mineral carbonation of the mine waste material. Geochemical assessment indicated that mean metal(loid) concentrations were found in the order of Al > Fe > Sr > Pb > Mn > Zn > As > Cd > Cu > Ni > Cr > Co in which Cd, Pb and As exceeded some regulatory guideline values. Ecological risk assessment demonstrated that the mine wastes were majorly influenced by Cd as being classified having moderate risk. Geochemical indices depicted that Cd was moderately accumulated and highly enriched in some of the mine waste deposited areas. In conclusion, the limestone mine waste material has the potential for sequestering CO2; however, the presence of some trace metals could be another important aspect that needs to be considered. Therefore, it has been shown that limestone mine waste can be regarded as a valuable feedstock for mineral carbonation process. Despite this, the presence of metal(loid) elements should be of another concern to minimize potential ecological implication due to recovery of this waste material.